#### Answer

y = $2x^{5}$ - $\frac{1}{2}$$x^{4}$ + C

#### Work Step by Step

$\frac{dy}{dx}$ = $10x^{4}$ - $2x^{3}$
$\int$dy = $\int$($10x^{4}$ - $2x^{3}$) dx
y = $2x^{5}$ - $\frac{1}{2}$$x^{4}$ + C

Published by
Brooks Cole

ISBN 10:
1-28505-709-0

ISBN 13:
978-1-28505-709-5

y = $2x^{5}$ - $\frac{1}{2}$$x^{4}$ + C

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.